Influence of Growth Regulators on Quality and Fruit Attributes of Custard Apple (Annona squamosa L.) Cv. Balanagar - Thorat, U. K.; Dheware, R. M.; Jadhav, A. R. (International Journal of Economic Plants, 2018)
The field study was conducted on a well-established custard apple orchard of eight years age at Custard Apple Research Station, Ambajogai, Dist. Beed, during 2016–17, to study the influence of growth regulators on quality and fruit attributes of custard apple (Annona squamosa L.) Cv. Balanagar. The experiment framed was concentrated to find out effective concentration of GA3 and NAA as well as their combination for getting high quality of custard apple fruits.The maximum length of fruit, diameter of fruit, weight of pulp, weight of peel was recorded under the treatment T7 (GA3 25+NAA 10 ppm). In present study, it had been observed that the foliar application of growth regulators was found beneficial for increasing quality of custard apple fruits. While, the combine spraying of GA3 25+NAA 10 ppm twice i.e. before flowering (second fortnight of may) and one month after the first spray is beneficial for getting higher quality of custard apple Cv. ‘Balanagar’ under Marathwada region of Maharashtra